Practitioner review: health anxiety in children and young people in the context of the COVID-19 pandemic. Issue 2 (18th March 2021) - Haig-Ferguson, A.; Cooper, K.; Cartwright, E.; Loades, M.E.; Daniels, J.
Abstract: Health-related fear is a normal and common response in the face of the global pandemic of COVID-19. Children and young people are frequently being exposed to messages about the threat to health, including from the media and authorities. Whilst for most, their anxiety will be proportionate to the threat, for some, existing pre-occupation with physical symptoms and illness will become more problematic. There is a growing body of evidence that health anxiety may occur in childhood, however much of the literature is taken from research using adult samples. This practitioner review aims to give an overview of the assessment and treatment of health-related worries in children and young people in the context of the COVID-19 pandemic. This review is based on the limited existing evidence in this population and the more substantial evidence base for treating health anxiety in adults. We consider the adaptations needed to ensure such interventions are developmentally appropriate.